1994
DOI: 10.1007/bf00686673
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy consisting of arterial infusion chemotherapy (EPF, EAP) and transcatheter arterial embolization (TAE)

Abstract: From January 1988 to January 1993, 45 patients with unresectable advanced hepatocellular carcinoma (HCC) were treated with a new combination therapy consisting of arterial infusion chemotherapy and TAE. The combination therapy was performed according to our treatment schedule as follows: two courses of arterial infusion chemotherapy were given first, and then transcatheter arterial embolization (TAE) using a mixture of Lipiodol and cisplatin powder was performed. Two arterial infusion chemotherapeutic regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A previous study[ 40 ] combined local treatment methods and showed that combination therapy consisting of HAIC (EPF [etoposide, cisplatin, and 5-FU] and EAP [etoposide, adriamycin or epi-adriamycin, and cisplatin]) and TACE was better than transarterial embolization alone for unresectable advanced HCC. Several studies[ 41 , 42 ] have explored HAIC in advanced HCC with PVTT and reported survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study[ 40 ] combined local treatment methods and showed that combination therapy consisting of HAIC (EPF [etoposide, cisplatin, and 5-FU] and EAP [etoposide, adriamycin or epi-adriamycin, and cisplatin]) and TACE was better than transarterial embolization alone for unresectable advanced HCC. Several studies[ 41 , 42 ] have explored HAIC in advanced HCC with PVTT and reported survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…We selected etoposide, carboplatin, epirubicin and pharmacokinetic modulating chemotherapy by 5-FU and enteric-coated tegafur/uracil. Firstly, etoposide is agent which has shown significant antitumor against HCC [14][15][16] . It could be suggested as part of intensive multidrug regimens for HCC and highrisk HBV [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%